Analisis Ketergantungan Guru IPA terhadap Buku Teks dan Implikasinya pada Inovasi Pembelajaran di Madrasah Ibtidaiyah - Hayaturraiyan (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the form and level of dependence of science teachers in Madrasah Ibtidaiyah on textbooks and its implications for learning innovation. The approach used is qualitative with a phenomenological design to explore teachers' subjective experiences and meanings in using textbooks as the main source of learning. Data were collected through interviews, observations, and document analysis from four science teachers at Madrasah Ibtidaiyah. The research results show that teachers' dependence on textbooks is still high due to factors such as limited competence, administrative pressure, a school culture that emphasizes compliance, and minimal support for learning facilities. This condition has an impact on low innovation and the lack of development of exploration based learning and direct experience.  Theoretically, this study confirms the relationship between dependence on textbooks and low pedagogical creativity of teachers in implementing the principles of independent learning